State versus market in the early historiography of the industrial revolution in Britain c.1890–1914. Issue 6 (1st November 2016) - Howe, Anthony
Abstract: This article reveals how the emerging historiography of industrialisation in Britain moulded a lasting division between two explanations of its origins, one emphasising discontinuity, individual enterprise, and free markets, the other evolutionary change, the role of the state and the importance of empire. Both views were historically informed but led in contrary directions in the highly polarised politics of early twentieth-century Britain, the former linked to support for free trade and liberalism as the basis of economic welfare, the latter to support for Conservative tariff reform and imperial reconstruction.